A structured review of patient‐reported outcome measures for patients with skin cancer, 2013. (5th June 2013) - Gibbons, E.; Casañas i Comabella, C.; Fitzpatrick, R.
Summary: Background: The collection of patient‐reported outcome measures (PROMs) within the national PROMs programme for elective procedures is now established mandatory practice in the NHS with high response rates and completion. Objectives: This review examines the evidence of PROMs for people with skin cancer. Methods: Comprehensive searches were conducted using several sources and databases, using a detailed search strategy developed by the University of Oxford's PROM Group. Articles were assessed for eligibility. Data were extracted per PROM for each measurement property and appraised using an appraisal framework. Results: A total of 3517 articles were identified in the searches, and 28 were included in the final review after assessment by two independent reviewers. Two generic instruments (SF‐36 and Sickness Impact Profile) and nine condition‐specific PROMs were identified. Conclusions: Overall, there is a limited volume of published evidence for the application of generic PROMs for people with skin cancer. Evaluation of the EQ‐5D may be particularly important given its widespread use in many other healthcare contexts in the U.K. The Skin Cancer Index could be considered for piloting in the NHS. For patients with nonmelanoma skin cancers, the Skindex measures may also be considered. The SCQOLIT has some evidence of applicability across both skin cancer types but more evaluations are needed. The FACT‐M does have more promising characteristics for patients with malignant melanomas although no evidence of testing in the U.K. was found. The forthcoming EORTC‐M may prove a useful measure given the expertise and track record of this European collaboration in cancer and quality of life. Abstract : What's already known about this topic? Patient‐reported outcome measures (PROMs) are an important feature of government plans to incorporate patients' perspectives of their health as an indicator of quality. PROMs have a long history in cancer research as an outcome measure and use in clinical practice for individual monitoring. The National PROMs programme for elective procedures achieves high response rates and several pilots are in progress in other conditions. Skin cancer is becoming a common cancer with associated morbidity, specifically malignant melanoma. What does this study add? This review provides evidence of measurement criteria for PROMs available for skin cancers. There is limited evidence to support the implementation of existing generic measures. Several promising PROMs are available for skin cancer but further evaluation and piloting is needed. See also the Commentary by Black